2003
DOI: 10.1210/jc.2002-022043
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of 7α-Methyl-19-Nortestosterone Implants for Possible Use as a Long-Acting Contraceptive for Men

Abstract: Several preparations of testosterone and its esters are being investigated alone or in combination with other gonadotropin-suppressing agents as possible antifertility agents for men. We studied the effectiveness of 7 alpha-methyl-19-nortestosterone (MENT) as an antispermatogenic agent in men. MENT has been shown to be more potent than testosterone and to be resistant to 5 alpha-reduction. For sustained delivery of MENT, we used a system consisting of ethylene vinyl acetate implants containing MENT acetate (Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 36 publications
3
58
0
2
Order By: Relevance
“…It is also important to mention that although MENT does not undergo further metabolism to 5a-reduced metabolites, reduction of the 4-ene-double bond of LNG and NET does not change Transcriptional androgenicity of MENT significantly their androgenic transcriptional activities (Sundaram et al 1995, Garcia-Becerra et al 2004) so as to have unwanted effects upon the prostate. Our results may also support promising approaches for male fertility regulation in terms of raising the dose of progestins to improve sperm suppression and minimize MENT nonreproductive androgenic effects (Anderson & Baird 2002, von Eckardstein et al 2003, Walton et al 2007.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…It is also important to mention that although MENT does not undergo further metabolism to 5a-reduced metabolites, reduction of the 4-ene-double bond of LNG and NET does not change Transcriptional androgenicity of MENT significantly their androgenic transcriptional activities (Sundaram et al 1995, Garcia-Becerra et al 2004) so as to have unwanted effects upon the prostate. Our results may also support promising approaches for male fertility regulation in terms of raising the dose of progestins to improve sperm suppression and minimize MENT nonreproductive androgenic effects (Anderson & Baird 2002, von Eckardstein et al 2003, Walton et al 2007.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, Walton et al (2007) showed that combination of MENT with a progestin resulted in rapid inhibition of spermatogenesis similar to the combined testosterone formulation and pointed out the importance of the synthetic progestin dose over the androgen dose in improving spermatogenesis suppression. However, subjects treated with four MENTimplants exhibited higher and longer spermatogenesis suppression (von Eckardstein et al 2003) than subjects treated with two MENT implants plus two ENG implants (Walton et al 2007). Four MENT implants induced azoospermia or severe oligozoospermia (sperm count !1!10 6 /ml) in 82% and 100% of subjects during the first and second 6-month periods of treatment respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A dose response trial of 7a-methyl-19-nortestosterone (MENT) was initiated in 35 healthy volunteers to assess effects of serum gonadotropins and sperm production. 52 This synthetic androgen is more potent than testosterone, is resistant to 5 a-reduction and has diffusion characteristics that make it wellsuited for a depot implant. Initial data showed relatively good efficacy, but typical testosteronerelated side effects.…”
Section: Testosterone Alonementioning
confidence: 99%